Analisis dan Pengurangan Aktivitas Tidak Bernilai Tambah Pada Sistem Produksi Manufaktur Skala Kecil Menggunakan Value Stream Mapping: Studi Kasus pada PT Veteri Nutri Animalia - Nugraha Raihan Alkabir Chairaza; Yenni Trisno (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study is motivated by the high level of operational inefficiencies in small-scale manufacturing, which are primarily caused by the presence of non-value-added activities and the use of push-based production systems. The objective of this study is to identify and reduce non-value-added activities in the production system of PT. VNA using the Value Stream Mapping (VSM) approach. This research employs a qualitative case study method through direct observation, interviews, and documentation of production processes. The analytical tools used include Value Stream Mapping (VSM), Process Activity Mapping (PAM), and VALSAT to map the current state and identify dominant waste. The results indicate that only 32.83% of the total production time constitutes value-added activities, while the remaining time is dominated by waiting and inventory accumulation. In addition, the reliance on forecast-based production contributes to overproduction and the buildup of work-in-process. A future state map is developed to reduce non-value-added activities through process simplification, improved scheduling, and better synchronization across production stages. This study concludes that the implementation of Value Stream Mapping provides a structured approach to improving operational efficiency in small-scale manufacturing by systematically identifying and reducing waste. Keywords: value stream mapping; non-value-added activities; production efficiency; small-scale manufacturing; lean manufacturing